EVALUASI PENGELOLAAN BANK SAMPAH PADA INSTITUSI PENDIDIKAN SEKOLAH DASAR WILAYAH KECAMATAN SUKOLILO SURABAYA - Dyah Kusuma Restienti; Waluyo Jati; Marlik . (Poltekkes Kemenkes Surabaya, 2015)
Waste management is a systematic activity, thorough and covering unfinished simultaneous reduction andwaste management. Waste management is not only done at the household level but also performed for aneducational institution that is in elementary school. waste management program is one of the primary schoolk tire waste. The purpose of this study is to evaluate the implementation of waste bank management ineducational institutionsof Elementary School in the District Sukolillo Surabaya.This study includes a descriptive study. Data collected by measuring, observations, questionnaires andinterviews. The sample in this study there are four primary schoolsthat run programs waste bank.The results of research on the 4 primary schools found that the source of waste collected to the school comesfrom two places, namely home and school. Types of waste collected include plastic bottles, waste paper, oldnewspapers. used plastic bottle caps, beverage glass former, the former color plastic, former color plastic,former glass bottles, cardboard and a small former used beverage cans. Waste buildup for each day isdifferent on the 4th. For maximum paper waste obtained at 9.400 gr / 30 days and obtained a minimum of 0gr / 30 pant and plastic waste obtained at 7,300 g / day and minimum 30 acquired 200 g / 30 pant.Mechanism of action of waste bank on 4th still less qualified predefined the Minister Regulation LH No. 13 In2012. The waste bank mechanism work point that has not qualified for the activity that is the result of thesale between p e and depositors of banks like waste. Student involvement in waste management is only partof the student involved. The level of knowledge of the bank responsible for managing the waste is still therethat have category enough. Responsiblefor managing the waste bank's actions still worth less good.It is recommended that each elementary school are encouraged to bring waste from home. Working with theWaste Bank independently that kind of waste collected more varied kinds Limiting students in using plasticand paper should be an increase in the bank management waste bank to the mechanism of action inaccordance with Minister Regulation LH No. 13 Year 2012 Solicitation for all students to be able to managethe waste so that it can be applied at home